2011
DOI: 10.1007/s00467-011-1993-8
|View full text |Cite
|
Sign up to set email alerts
|

Dosing of glucocorticosteroids in nephrotic syndrome

Abstract: SummaryPharmacodynamic actions and molecular mechanisms of corticosteroids in patients with nephrotic syndrome (NS) are poorly understood. The role of immunosuppressive and of direct stabilizing effects on the podocyte cytoskeleton needs to be defined. Without precise knowledge of the pathogenesis, optimal dosing cannot be established. The finding of Saadeh et al. [1] that dosing of glucocorticoids per body surface area is superior to dosing per kilogram body weight (BW) in terms of reducing the recurrence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
(33 reference statements)
0
7
1
Order By: Relevance
“…Recent studies have shown that the PDN dose of 2 mg/kg/day or 60 mg/m 2 /day cannot be considered equivalent for patients who weigh <30 kg [11]. Whether these different choices in PDN dosing have clinicl relevance is still a matter of debate [12, 13]; however, we decided to adopt the same dosage (body surface area dosing) for all our patients in order to avoid any hypothetical bias when evaluating the results of the therapy.We suggest that PDN be given at 60 mg/m 2 /day, with a maximum dose of 60 mg/day. …”
Section: Corticosteroid Use For the First Episode Of Insmentioning
confidence: 99%
“…Recent studies have shown that the PDN dose of 2 mg/kg/day or 60 mg/m 2 /day cannot be considered equivalent for patients who weigh <30 kg [11]. Whether these different choices in PDN dosing have clinicl relevance is still a matter of debate [12, 13]; however, we decided to adopt the same dosage (body surface area dosing) for all our patients in order to avoid any hypothetical bias when evaluating the results of the therapy.We suggest that PDN be given at 60 mg/m 2 /day, with a maximum dose of 60 mg/day. …”
Section: Corticosteroid Use For the First Episode Of Insmentioning
confidence: 99%
“…However, not all patients show positive response to the therapy and approximately 10-20% of patients don't respond to it. The variety of reactions to this therapy divides the patients to steroid sensitive (SS) and steroid resistant (SR) (Mehls & Hoyer, 2011;Abid et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Actions of glucocorticoids (GCs) include the genomic and nongenomic mechanisms. Genomic reactions of GCs are associated with glucocorticoid receptor α (GR) (Gross et al, 2009;Mehls & Hoyer, 2011). Nongenomic mechanisms include interactions of GCs with cell membrane, cytosolic GR and with cell membrane-bound GR (Smoak & Cidlowski, 2004;Stahn & Buttgereit, 2008;Alangari, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the limitations of these findings were described, such as the overriding effect of age or short observation period [2], the hypothesis that BW-based dosing would result in altered treatment outcomes is very interesting. To investigate whether the two dosing regimens might not be equivalent, we therefore retrospectively reviewed the medical records of children diagnosed with idiopathic NS at our institution.…”
mentioning
confidence: 99%